Artificial intelligence and the future of humanity : critical reflections on the social ethical and religious impact of AI - Job Kozhamthadam Ed; Jayard Stephen S (Delhi Indian Institute of Science and Religion, 2024)
We are fortunate to live in an age that is witnessing such unprecedented strides in science, ingeniously assisted by technology, that the claim is made that it is only a matter of time when human scientific prowess will have made in its laboratory not only living beings, including humans, but also superhumans or posthumans. As we rejoice and applaud the amazing achievements of our scientists, the real question is whether or how far will they be able to deliver their claim. Several well-informed authors, in their well-researched papers of this seventeen-paper volume, point out the formidable challenges still awaiting Artificial Intelligence (AI) experts.
Keywords: Artificial Intelligence Dawn and Development; Artificial Intelligence Social and Ethical Perspectives; Artificial Intelligence a Platform for Science Religion Dialogue